Geological characteristics of the boundary between Bolkardağı-Bozkır Units and the Ulukışla Basin and the structural evolution of the region, Central Taurides, Turkey - Veysel Işık; Tolga Esirtgen (Bulletin of the Mineral Research and Exploration, 2021)
The character of the boundary between the tectonic units in the Central Taurides and the Ulukışla Basin is controversial. The contact has been accepted as discordant or tectonic contact by different researchers. The deformation data of the units in the study area provide important information about the Mesozoic - Cenozoic period geological developments of the region. Regional compression in NW - SE direction has caused the development of fold, foliation and reverse fault type structures in the units in the study area. Similar structural deformations are observed in the rock units defined in the Ulukışla Basin as well. In this study, structural data were collected from the field in order to determine the deformation pattern and contact relations of the units in the region. Field data and structural analysis reveal that the  contact between the Ulukışla Basin deposits and the Bolkardağı Unit in the study area is of 70° - 80° southeast dipping reverse fault character. These structural data in the region were interpreted as the product of a movement from southeast to northwest.